The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10834-006-9038-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of American Media Exposure and Self-Esteem on Chinese Urban Adolescent Purchasing Involvement

Abstract: This study based on a sample of 429 Beijing high school students shows that Chinese urban adolescents’ purchasing involvement can be predicted by the adolescents’ self-esteem. Individuals’ self-evaluation motivates them to get involved in family purchasing activities. This study suggests that Chinese consumer involvement is potentially shaped by both cognitive factors (e.g., self-esteem) and social factors (e.g., media use). However, the study indicates that exposure to American mass media does not have signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…' (McEwen et al, 2006, p. 76). Dong and Cao (2006) found that a cognitive factor (i.e. self-esteem) plays an important role in shaping Chinese consumers' involvement.…”
Section: Svs: a Universal Consumer Value Structurementioning
confidence: 98%
See 1 more Smart Citation
“…' (McEwen et al, 2006, p. 76). Dong and Cao (2006) found that a cognitive factor (i.e. self-esteem) plays an important role in shaping Chinese consumers' involvement.…”
Section: Svs: a Universal Consumer Value Structurementioning
confidence: 98%
“…Chinese consumers are living in ‘a new era in which the emotions, attitudes, and perceptions of the man and woman on the street increasingly matter.’ (McEwen et al ., 2006, p. 76). Dong and Cao (2006) found that a cognitive factor (i.e. self‐esteem) plays an important role in shaping Chinese consumers' involvement.…”
Section: Literature Reviewmentioning
confidence: 99%